Molecular Diagnostics for Gonorrhoea: Implications for Antimicrobial Resistance and the Threat of Untreatable Gonorrhoea - Low, Nicola (Public Library of Science, 2014)
This Essay from Nicola Low and colleagues discusses the importance of the nucleic acid amplification tests for rapid detection of N. gonorrhoeae and its resistance determinants, as well as the importance of ensuring their rational use, as priorities for controlling both gonorrhoea and antimicrobial resistance. Please see later in the article for the Editors' Summary